2016
DOI: 10.1159/000445861
|View full text |Cite
|
Sign up to set email alerts
|

Internet Information for Patients on Cancer Diets - an Analysis of German Websites

Abstract: Background: In recent years, the Internet has become an important source of information for cancer patients. Various cancer diets that are publicized on the Web promise significant benefits. The aim of our study was to evaluate the quality of online patient information about cancer diets. Materials and Methods: A patient's search for ‘cancer diets' on German websites was simulated using the search engine Google. The websites were evaluated utilizing a standardized instrument with formal and content aspects. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 27 publications
1
21
1
Order By: Relevance
“…However, our study did not identify significant differences for most quality aspects between websites of for-profit and non-profit organizations. This contrasts with the results of the studies by Liebl and colleagues, and Herth and colleagues, which found significant differences regarding almost all quality aspects for for-profit and non-profit providers [11,14]. In our study, online newspapers scored significantly lower on the overall score and on all contentrelated items.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…However, our study did not identify significant differences for most quality aspects between websites of for-profit and non-profit organizations. This contrasts with the results of the studies by Liebl and colleagues, and Herth and colleagues, which found significant differences regarding almost all quality aspects for for-profit and non-profit providers [11,14]. In our study, online newspapers scored significantly lower on the overall score and on all contentrelated items.…”
Section: Discussioncontrasting
confidence: 99%
“…Herth and colleagues analyzed internet information for patients on cancer diets [ 14 ]. In their analysis, self-help groups and non-profit organizations ranked highest.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…All healthcare professionals in this study discussed diets and fad diets amongst their patients with cancer and indicated that most of the harmful diet-related information patients presented was from the Internet. This is corroborated in the broader literature, where a recent analysis of over 30 websites of cancer diet information found discrepancies between for-profit and not-for-profit websites, highly variable information and information that is difficult for patients to sift through (Herth et al, 2016). Clearly, patients need assistance finding the right information, particularly given the concerns raised by numerous professionals.…”
Section: Discussionmentioning
confidence: 70%
“…Consequently, the Internet has removed many barriers to access health information [ 21 , 22 ]. However, the broad offers of information can be challenging and difficult to filter and comprehend, especially since there is often a discrepancy between the accessibility and quality of information, which then, in turn, can lead to wrong decisions [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%